2024
DOI: 10.1021/acsami.3c11743
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Critical Catalyst Layer Phenomena toward High Production Rates for the Electrochemical Conversion of CO to Ethylene

Danielle Henckel,
Prantik Saha,
Fry Intia
et al.

Abstract: This work utilizes EIS to elucidate the impact of catalyst−ionomer interactions and cathode hydroxide ion transport resistance (R CL , OH − ) on cell voltage and product selectivity for the electrochemical conversion of CO to ethylene. When using the same Cu catalyst and a Nafion ionomer, varying ink dispersion and electrode deposition methods results in a change of 2 orders of magnitude for R CL , OH − and ca. a 25% change in electrode porosity. Decreasing R CL , OH − results in improved ethylene Faradaic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The chemistry of the ionomer can affect the hydrophobicity of the catalyst layer, ion conductivity, and reactant gas permeability . The conformation of the ionomer can also be influenced by the catalyst ink , and deposition method, netting changes in competitive adsorption processes and local gas transport. Significantly thick ionomer films can result in underutilized catalyst sites, where reactant gases are forced around areas with low permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of the ionomer can affect the hydrophobicity of the catalyst layer, ion conductivity, and reactant gas permeability . The conformation of the ionomer can also be influenced by the catalyst ink , and deposition method, netting changes in competitive adsorption processes and local gas transport. Significantly thick ionomer films can result in underutilized catalyst sites, where reactant gases are forced around areas with low permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) was used to elucidate the maximum available electrochemical surface area as a function of RH. Catalyst utilization describes the fraction of catalyst that is available to the electrochemical reaction (for discussion, see refs and ).These experiments were performed as previously described (Figure S12). Briefly, we will measure the EIS in a region where no or little charge transfer is occurring.…”
Section: Introductionmentioning
confidence: 99%
“…As it happens in electrochemical systems where both ionic transport and electrical interactions are crucial for the reaction outcomes, in zeolite catalysts, these characteristics can affect the diffusion of reactants and When discussing electrical and plasma interactions in such catalytic systems, it is useful to look at the wider meaning of ionic conductivity and its impact on catalytic processes. The work of Henckel et al [78] is a relevant example of this, as they used Electrochemical Impedance Spectroscopy (EIS) to investigate the interaction between the catalyst and ionomer, with a particular interest in the transport of hydroxide ions in the electrochemical CO to ethylene conversion. The results confirmed that fine-tuning ionic conductivity can substantially promote the Faradaic efficiency of ethylene and the cell voltage.…”
Section: Electrical and Plasma Interactionsmentioning
confidence: 99%
“…al. [37] utilized Electrochemical Impedance Spectroscopy (EIS) for investigating the interplay between the catalyst and ionomer, as well as the resistance to the transport of hydroxide ions at the cathode, in the process of converting CO to ethylene electrochemically. Their work showed that the selection of the optimal synthesis conditions and factors such as the ionic conductivity brought improved ethylene Faradaic efficiency and cell voltage.…”
Section: Electrical and Plasma Interactionsmentioning
confidence: 99%